Detente and defense : a reader - Pranger, Robert J. (Washington : American Enterprise Institute for Public Policy Research, 1976)
This book presents a collection of articles and documents relating to the diplomatic and defense objectives of the United States of America in its relations with the Soviet Union, Eastern Europe, and the People's Republic of China.
Includes bibliographical references.
asm 22/01/2019
Loans
Keywords: Detente; Military readiness; Diplomatic relations; United States